Mesenchymal stem cells ameliorate inflammation and pyroptosis in diabetic cardiomyopathy via the miRNA-223-3p/NLRP3 pathway - Yang Qu; Qi Chen; Sihui Li; Jun Luo (2024)
Abstract Background Diabetic cardiomyopathy (DCM) stands as the primary cause of heart failure and mortality among patients with diabetes. Nevertheless, conventional treatment approaches are limited in their ability to effectively prevent myocardial tissue damage itself. Mesenchymal stem cell (MSC) therapy exhibits immense potential for treating DCM; however, the precise mechanisms involved in regulating inflammatory responses and pyroptosis processes, an emerging form of cellular death, within myocardial cells remain elusive. Hence, it is imperative to further elucidate the precise underlying mechanisms to facilitate the clinical implementation of MSC therapy. Methods In vivo, we established a DCM mouse model by administering streptozotocin and fed the mice a high-glucose and high-fat diet, followed by MSC therapy. Cardiac function and myocardial injury were evaluated through echocardiography and histological analysis. Furthermore, the levels of inflammation and pyroptosis were assessed using ELISA, Western blotting, and qRT-PCR. In vitro experiments involved inducing H9C2 myocardial cell damage with high glucose treatment, followed by coculture with MSCs to investigate their role in modulating inflammation and pyroptosis mechanisms. Results MSCs can maintain cardiac function and alleviate myocardial injury in mice with DCM. Moreover, they effectively suppress the activation of NLRP3 and reduce the release of inflammatory factors (such as IL-1β and ROS), thereby further downregulating the expression of pyroptosis-related proteins including NLRP3, Caspase-1, and GSDMD. Additionally, we experimentally validated that MSCs exert their therapeutic effects by promoting the expression of miR-223-3p in cardiac myocytes; however, this effect can be reversed by an miR-223-3p inhibitor. Conclusion MSCs effectively mitigate the release of inflammatory factors and cell lysis caused by pyroptosis through the regulation of the miR-223-3p/NLRP3 pathway, thereby safeguarding cardiomyocytes against damage in DCM. This mechanism establishes a novel theoretical foundation for the clinical treatment of cardiac conditions utilizing MSCs.